COVID-19 Infection Deteriorates the Clinical Condition and Outcomes of Acute Pancreatitis: A Meta-Analysis. (28th October 2022) - Guo, Yulin; Hu, Shun; Wang, Xiaohui; Jiang, Zhe; Duan, Shuangni; Cao, Feng; Li, Fei
Abstract : Backgrounds . The novel coronavirus disease 2019 (COVID-19) has caused a global pandemic. Pancreatic injuries have been reported in COVID-19 patients. The present meta-analysis was conducted to compare the morbidity and outcomes of AP between COVID-19 positive and negative patients. Methods . Databases including Cochrane Library, PubMed, and EMBASE were systematically searched (until July 3rd 2022). Studies with English abstracts comparing the severity and outcomes of AP between COVID-19 positive and negative patients were included. Mean differences or odds ratios with a 95% confidence interval were employed for assess variables. Risk of publication bias was assessed with funnel plots. Results . Data from 7 studies with a total of 2816 AP patients were included. COVID-19 positive was associated with higher incidences of pancreatic necrosis (OR = 1.65; 95% CI: 1.13 to 2.42, P  = 0.01; P  = 0.82 for heterogeneity) and persistent organ failure (OR = 6.87; 95% CI: 2.37 to 19.98, P  = 0.0004; P  = 0.12 for heterogeneity), especially cardiovascular failure (OR = 2.92; 95% CI: 1.66 to 5.14, P  = 0.0002; P  = 0.58 for heterogeneity) and acute respiratory distress syndrome (ARDS) or acute lung injury (ALI) (OR = 3.03; 95% CI: 2.09 to 4.39, P  < 0.00001; P  = 0.20 for heterogeneity). COVID-19 infection induced a higher level of CRP (MD = 0.40; 95% CI: 0.16 to 0.64, P  = 0.001; P  < 0.00001 for heterogeneity) as well as coagulation disorders involving platelets, prothrombin time, activated partial thromboplastin time, and D-dimer (all P  < 0.05). During hospitalization, COVID-19 positive was associated with higher ICU admission rate (OR = 2.76; 95% CI: 1.98 to 3.85 P  < 0.00001; P  = 0.47 for heterogeneity). COVID-19 positive AP was associated with a higher mortality rate (OR = 3.70; 95% CI: 2.60 to 5.25, P  < 0.00001; P  = 0.12 for heterogeneity). Discussion . The number of included studies is limited and none is RCT, thus the risks of publication and selective bias could not be ignored. COVID-19 deteriorated the severity and clinical outcomes of AP, with a high incidence of morbidity and mortality.